Traditional and Non-traditional Cardiovascular Risk Factors and Cardiovascular Disease in Women with Psoriasis - Charlotte Näslund-Koch; Signe Vedel-Krogh; Stig Egil Bojesen; Lone Skov (Medical Journals Sweden, 2022)
Women with cardiovascular disease are underdiagnos-ed, undertreated and under-represented in research. Even though the increased risk of cardiovascular disease among patients with psoriasis is well establi-shed, only a few studies have examined women with psoriasis. This study examined the prevalence of cardio-vascular risk factors and cardiovascular disease among women with psoriasis. Using the Copenhagen City Heart Study and the Copenhagen General Population Study, 66,420 women were included in a cross-sectional design. Of these, 374 (0.56%) women had hospital-diagnosed psoriasis. Women with vs with-out hospital-diagnosed psoriasis had higher odds ratios of having traditional cardiovascular risk factors, including hypertriglyceridaemia, smoking, obesity, type 2 diabetes, and low physical activity, and of having non-traditional cardiovascular risk factors, including low level of education, high level of psycho-social stress, and low-grade inflammation. Compared with women from the general population, the multi-variable adjusted odds ratio of heart failure and ischaemic cerebrovascular disease in women with hospital-diagnosed psoriasis was 2.51 (95% confidence interval 1.33-4.73) and 2.06 (1.27-3.35). In conclusion, women with hospital-diagnosed psoriasis have a higher prevalence of traditional and non- traditional cardiovascular risk factors, and increased risk of heart failure and ischaemic cerebrovascular disease, even after adjusting for these cardiovascular risk factors.